Perbaikan Tata Letak Fasilitas Gudang Guna Menekan Ongkos Material Handling Pada CV. SG - Prima, Jupiter Yulio; Mundari, Siti (Fakultas Teknik Universitas Tulang Bawang, 2025)
CV. SG is a company engaged in the distribution of bottled cooking oil, including the Minyakita product. However, an unstructured facility layout has led to various challenges, particularly in operational efficiency and material handling costs. Inefficient placement of goods and lack of attention to material movement distances have resulted in increased operational expenses and prolonged processing times. These inefficiencies can hinder productivity and add to the workload, especially in routine material handling activities involving frequent movement of goods.To address these issues, this study focuses on redesigning the warehouse layout with the primary objective of optimizing material movement distances and reducing material handling costs. The method employed in this research is quantitative analysis, which includes calculating transfer distances, movement frequency, material handling moments, and cost estimation.The findings indicate that the initial layout incurred a total material handling cost of IDR 2,860,000 per month, with a total movement distance of 300.80 meters. After the redesign, the proposed layout successfully reduced the movement distance to 241.17 meters, leading to a decrease in material handling costs to IDR 2,761,200 per month. Thus, the implementation of the new layout has proven to be more efficient in reducing costs and enhancing the effectiveness of material movement within the warehouse. Keywords: Layout, Material Handling, Warehouse